A forgotten pathology among biliary tract cysts: cystic dilatation of the cystic duct - Ahmet Baytok; Gökhan Ecer (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Cystic duct cysts, also known as Type VI choledochal cysts, are extremely rare congenital biliary anomalies. Due to their nonspecific clinical presentation and imaging similarities with other biliary cystic diseases, they are frequently misdiagnosed preoperatively, which may result in suboptimal surgical planning and management. Case presentation We report the case of a 24-year-old female who presented with several months of intermittent right upper quadrant pain and renal colic to urology clinic, especially after consuming fatty meals. Imaging with ultrasound and MRCP revealed a 3 × 2 cm cystic dilatation of the cystic duct. No signs of malignancy were observed on diffusion-weighted imaging or ADC maps. The patient declined surgery and opted for regular follow-up. After 1 year, no progression or malignant transformation was observed on repeat imaging. Discussion The diagnosis of cystic duct cysts can be challenging due to their overlapping features with more common choledochal cysts, particularly Type II cysts. A multidisciplinary approach involving radiologists, surgeons, and gastroenterologists is essential for accurate diagnosis. Surgical treatment is typically recommended to prevent complications such as recurrent cholecystitis or malignant degeneration. However, our case suggests that conservative management may be a viable option in select patients with stable imaging and no concerning features. Conclusion Although rare, cystic duct cysts should be considered in the differential diagnosis of biliary cystic lesions. Accurate preoperative identification and appropriate surgical planning are critical for optimal outcomes. This case also underscores the potential role of non-surgical management with close follow-up in selected, low-risk patients.